Efficacy of Whole System Approach Ayurveda Interventions in Vibhanda W. S. R. Old Age Constipation - A Randomized Control Clinical Trial - Ramesh Shivappa Killedar; Savita Angadi; Uma Shetti; Meghana Patil; Pradeep S. Shindhe; Sheetal Kumar Bolaj (Wolters Kluwer Medknow Publications, 2024)
Introduction: Constipation in elderly individuals is typically complex, with co-morbid conditions. In Ayurveda, numerous plants and mixtures have been recommended for the treatment of Vibandha. In order to evaluate complementary and alternative medicine interventions that are too complicated to be studied using conventional research designs, notably the randomized controlled trial design, whole system research (WSR) has emerged as a new method. WSR is primarily focused on clinical medicine and places an emphasis on treating patients as individuals rather than in groups. Methods: A total of 60 patients with old age constipation, fulfilling inclusion criteria were recruited. Group A (Kalyanaka kshara [KK]) (control) and Group B (Trial) (WSR) based on kostha assessment were given for 10 days. ROME III criteria were used to assess the efficacy of KK and whole system approach (WSA) of Ayurveda interventions. The Wilcoxon match paired test and the Mann-Whitney U-test were used for the statistical analysis to compare the data between and within groups. Results and Conclusion: Within group results of both the group showed significant changes at all-time points (P < 0.005). Whole system approach of Ayurveda interventions has showed significant changes in between group results than the KK at all-time points (P < 0.005). The present study showed that whole system approach has showed promising results as the assessment of constipation and medicine prescription based on the kostha assessment plays a very important role.